A comprehensive approach to analyzing the XMM-Newton data of Seyfert 1 galaxies - Cardaci, Mónica Viviana (2011)
Aims. We seek a comprehensive analysis of all the information provided by the XMM-Newton satellite of the four Seyfert 1 galaxies ESO 359-G19, HE 1143-1810, CTS A08.12, and Mrk 110, including the UV range, to characterize the different components that are emitting and absorbing radiation in the vicinity of the active nucleus. Methods. The continuum emission was studied through the EPIC spectra by taking advantage of the spectral range of these cameras. The high-resolution RGS spectra were analyzed to characterize the absorbing and emission line features that arise in the spectra of the sources. All these data, complemented by information in the UV, are analyzed jointly in order to achieve a consistent characterization of the observed features in each object. Results. The continuum emission of the sources can be characterized either by a combination of a power law and a black body for the weakest objects or by two power law components for the brightest ones. The continuum is not absorbed by neutral or ionized material in the line of sight to any of these sources. In all of them we have identified a narrow Fe-Kα line at 6.4 keV. In ESO 359-G19 we also find an Fexxvi line at about 7 keV. In the soft X-rays band, we identify only one Ovii line in the spectra of HE 1143-1810 and CTS A08.12, and two Ovii-Heα triplets and a narrow Oviii-Lyα emission line in Mrk 110. Conclusions. Not detecting warm material in the line of sight to the low state objects is due to intrinsically weaker or absent absorption in the line of sight and not to a low signal-to-noise ratio in the data. Besides this, the absence of clear emission lines cannot be fully attributed to dilution of those lines by a strong continuum.